Number of Teeth and Incidence of Hip Fracture in Older Adults Aged ≥75 Years: The OHSAKA Study - Naoko Otsuki; Tomoaki Mameno; Yuya Kanie; Masahiro Wada; Maki Shinzawa; Kazunori Ikebe; Ryohei Yamamoto (Journal of Epidemiology, 2025)
Background: Several studies reported an association between the number of teeth and the incidence of hip fractures in observational studies, mainly in middle-aged adults. This retrospective cohort study aimed to clarify the association between the number of teeth and the incidence of hip fractures. Methods: In this retrospective cohort study, a total of 256,772 participants aged 75 years or older who underwent public dental checkups in Japan were evaluated. Exposure in this study was the number of teeth, with a maximum number of 28, excluding third molars. Outcome measures were the incidence of hip fractures needing surgery, using the Japanese procedure codes in medical claims. Results: A total of 190,998 participants met the inclusion criteria and were available for analysis. Adjusted Fine and Gray models identified a significant association between the number of teeth, including sound, filled, and decayed teeth, and the incidence of hip fractures among women but not for men. The continuous net reclassification improvement of the sound and filled teeth count model increased by 0.078 compared with that of the sound, filled, and decayed teeth count model among women. Conclusion: The number of sound and filled teeth predicted the risk of hip fractures in women, whereas no association was observed between the number of teeth and hip fractures in men.